Smart Irrigation untuk Optimalisasi Pertanian Sistem Green House pada Kelompok Petani Tani Sejahtera di Desa Temuasri, Banyuwangi - Mohammad Hamim Zajuli Al Faroby; Helisyah Nur Fadhilah; Regita Putri Permata; Muhammad Adib Kamali (I-Com: Indonesian Community Journal, 2025)
Smart irrigation technology is an innovation designed to improve the efficiency of water and fertilizer management in agricultural activities, especially in a greenhouse environment. This study aims to implement and evaluate the use of smart irrigation technology in Temuasri Greenhouse, which is known as one of the centers of melon cultivation with tabulampot system (fruit plants in pots). The system relies on a Programmable Logic Controller (PLC) and Human-Machine Interface (HMI) to automate the watering process and fertilizer distribution and facilitate real-time monitoring of irrigation conditions. The program involved 16 target communities who received training on the installation, operation, and maintenance of the smart irrigation system. Based on the evaluation results, the technology was successfully implemented, providing increased efficiency in water and labor use, while reducing direct contact during the watering process. The survey showed that 84.72% of participants gave very positive feedback, stating that this activity was effective, useful, and has great potential for further development. The successful implementation of smart irrigation technology is expected to become a reference for technology-based irrigation management models that support agribusiness sustainability, while increasing the productivity and quality of agricultural products in the future.